2020
DOI: 10.1002/ana.25740
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Elevated LDL Associates with Lower Risk of Intracerebral Hemorrhage

Abstract: Objective Observational studies point to an inverse correlation between low‐density lipoprotein (LDL) cholesterol levels and risk of intracerebral hemorrhage (ICH), but it remains unclear whether this association is causal. We tested the hypothesis that genetically elevated LDL is associated with reduced risk of ICH. Methods We constructed one polygenic risk score (PRS) per lipid trait (total cholesterol, LDL, high‐density lipoprotein [HDL], and triglycerides) using independent genomewide significant single nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 41 publications
4
32
0
Order By: Relevance
“…Along this lines, found a strong positive association between LDL-C and ischemic stroke and a strong inverse association with ICH in participants of the China Kadoorie Biobank. This inverse association between genetically determined LDL-C levels and the risk of ICH was confirmed in cohorts of European descent by Falcone et al (2020). The latter two studies confirmed previous observational results that suggested that very low LDL-C levels increase the risk of ICH (Wang et al, 2013;Saliba et al, 2018;Ma et al, 2019), pointing to novel pathways in ICH.…”
Section: Lipidssupporting
confidence: 83%
“…Along this lines, found a strong positive association between LDL-C and ischemic stroke and a strong inverse association with ICH in participants of the China Kadoorie Biobank. This inverse association between genetically determined LDL-C levels and the risk of ICH was confirmed in cohorts of European descent by Falcone et al (2020). The latter two studies confirmed previous observational results that suggested that very low LDL-C levels increase the risk of ICH (Wang et al, 2013;Saliba et al, 2018;Ma et al, 2019), pointing to novel pathways in ICH.…”
Section: Lipidssupporting
confidence: 83%
“…High concentrations of low-density lipoprotein (LDL) cholesterol have been associated with an increased risk of cerebral infarction but with a lower risk of hemorrhagic stroke [ 29 , 30 ]. An inverse association of milk product consumption with LDL to high-density lipoprotein cholesterol ratio has earlier been observed in a study of 70-year-old men [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The point estimate for haemorrhagic stroke in vegans compared to meat-eaters was 1⋅35, but this was not statistically significant. The cause of the higher risk of haemorrhagic stroke in vegetarians is not known, but it might be explained by the low LDL-cholesterol which has been associated with an increased risk in observational studies, Mendelian randomisation analyses and in lipid lowering trials using statins (21,22) ; it might also be related to other factors such as high homocysteine due to low vitamin B 12 , or possibly related to the low intake of animal protein, but further research is needed to examine these hypotheses.…”
Section: Major Diseases: Cvd and Diabetesmentioning
confidence: 99%